The multicriterial evaluation method of the effectiveness of the investment projects - Tamošiūnienė, Rima; Šidlauskas, Skirmantas; Trumpaitė, Ingrida (Business: Theory and Practice, 2006)
A large number of economic, financial, social, technological, ecological – environmental and other indicators define the effectiveness of the investment projects. According to some of the indicators, the alternative investment project is suitable for putting it into practice, according to others, it is not. Therefore, while evaluating the investment projects (e.g. the projects which are financed by EU structural funds) it becomes difficult to choose the most effective projects whose realization would bring the most significant benefit to the economy subject and to our country. It is possible to get objective answers about the effectiveness of the alternative investment projects by evaluating them according to multicriterial methods. With the help of such methods it is possible to evaluate the investment projects comprehensively by presenting one generalized indicator. It shows the effectiveness of the alternative project fairly objectively. The multicriterial evaluation method analyzed in the article gave the possibility to evaluate the effectiveness of the projects chosen, and to set the priority level of these projects. From the analysis carried out, it is obvious that three investment projects are suitable for being financed and put into practice, and the remaining ones have to be rejected or corrected. The method for evaluating the effectiveness of the investment projects proposed by the authors has both theoretical and practical advantages (the extensive analysis can be carried out, the different classification of the evaluation criteria is possible, the weight of the criteria is evaluated (importance, significance), the possibility to include the new evaluation criteria and their employment in practice (in the field of investment analysis) is considered. The obtained evaluation results of the investment projects show that the multicriterial evaluation method is good for evaluating complex processes such as the evaluation of the effectiveness of the alternative investment projects, and the method of the evaluation of the investment projects proposed can be adapted for various situations (e.g. evaluating investment projects which get EU means).Article in Lithuanian.Investicinių projektų efektyvumo daugiakriterinis vertinimasSantrauka. Investicinių projektų efektyvumą nusako daugelis ekonominių, finansinių, socialinių, technologinių, ekologinių, aplinkosauginių ir kitų rodiklių. Pagal vienus iš šių rodiklių alternatyvus investicinis projektas tinkamas įgyvendinti, o pagal kitus – netinkamas. Todėl vertinant investicinius projektus (pvz., projektus, finansuojamus ES struktūrinių fondų) sunku išrinkti efektyviausius projektus, kurių įgyvendinimas atneštų didžiausią naudą tiek jį įgyvendinančiam ūkio subjektui, tiek mūsų šaliai. Objektyvius atsakymus apie alternatyvių investicinių projektų efektyvumą galima gauti juos vertinant daugiakriteriniais būdais. Jie leidžia išsamiai ir kompleksiškai įvertinti investicinius projektus, pateikiant vieną apibendrinamąjį rodiklį, kuris gana objektyviai rodo alternatyvaus projekto efektyvumą. Straipsnyje nagrinėjamas daugiakriterinis efektyvumo vertinimo būdas leido įvertinti pasirinktų verslo projektų efektyvumą bei nustatyti šių projektų prioritetinę eilę. Iš atliktos analizės matyti, kad trys iš vertinamų investicinių projektų yra tinkami finansuoti ir įgyvendinti, o likę investiciniai projektai turėtų būti atmesti arba atiduoti koreguoti. Alternatyvių investicinių projektų efektyvumo vertinimo rezultatai parodė, kad daugiakriteriniai vertinimo būdai gali būti taikomi tokiems projektams vertinti, o kartu ir projektams, finansuojamiems ES struktūrinių fondų, vertinti.Reikšminiai žodžiai: investicijos, daugiakriterinis vertinimas, efektyvumas.